An experimental investigation on the performance of a single cylinder diesel engine at various partial loads - Thong Duc Hong; Binh Thanh Thi Hoang; Thien Quoc Mai Ho; Phat Tan Truong; Minh Quang Pham (Transportation Engineering)
This study investigates various partial load characteristics of a diesel engine, including brake specific fuel consumption, torque, and power, to get insight into these performances in practice. Firstly, these characteristics were experimentally examined with approximate 25, 50, 75, and 85 % fuel rack settings at 900–2400 rpm engine speeds. Then, more operating modes were investigated to build characteristics corresponding to constant fuel quantity per engine cycle. The results indicate that the practical partial load characteristics significantly differ from the theory of full-load characteristics since the fuel quantity per cycle varies even though the rack is fixed. Especially at low loads, the fuel quantity per cycle increases enormously with engine speed due to the significant influence of pressure waves. Hence, torque and power increase continuously, making it challenging to control the engine operation. In contrast, because the reduction in fuel viscosity and pump efficiency balances the pressure wave effects at high loads, fuel quantity per cycle remains relatively constant, making the characteristics more similar to the theory. Besides, if fuel quantity per cycle is kept constant, the trends in partial load curves follow the theory, which can be approximately predicted. These findings reveal that considering fuel quantity per cycle is significant when studying diesel engine partial loads, notably at low loads. The study contributes a vital basis for further investigating and modeling the partial characteristics of diesel engines. Also, it is a crucial reference for estimating the suitable working conditions of engine-driven systems in practice.